(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article explores the life, political activity and historical legacy of Cleopatra VII Philopator — the last queen of Ancient Egypt. It analyzes her background, alliances with Julius Caesar and Mark Antony, conflict with Rome, the Battle of Actium and her death, as well as Cleopatra’s role in global culture. The material is based on historical sources and modern research.